PERANCANGAN DESAIN PRODUK SPRING BED DENGAN MENGGUNAKAN METODE QUALITY FUNCTION DEPLOYMENT - Febi Ardani; Rosnani Ginting; Aulia Ishak (Jurnal Teknik Industri USU, 2014)
Business competition demands a company to apply a strategic plan to meet the needs of consumers in the development of products to improved quality, performance, and a reduction in costs and time of production. PT XYZ is one of the manufacturing company that produce spring bed products, keep trying to meet consumer needs with a high quality product. Problems that occur on company is redesign component product spring bed that cause the longer production time and the higher of the unit cost product. The purpose of this research is to identify the causes of the occurance of a waste of time and cost in the process of making product with Quality Function Deployment(QFD) method. QFD used to identify consumer needs that connects between technical characteristics of the product. Technical characteristics of products that have the highest value shows that these technical characteristics are the focus of the problem faced by the company, while the attributes of consumer needs that has the highest value are things that should be fixed to address existing problems. The result showed that performance of the technical characteristics with the highest value is part family and similarity in the base of the structure of component with each value degrees interests about 20 %, while the ten attributes of consumers needs that gain the highest relative weight is variable type of mattress foam with the value of relative weight about 16,29.